Knowledge and attitude of youth towards contact lenses in Karachi, Pakistan - Rafia Irfan; Roha Saeed Memon; Mahnoor Yousif Shaikh; Ilma Khalid; Nimra Shakeel; Eleze Tariq (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background Surveys have shown that contact lenses are common optical correction devices used worldwide and they are particularly popular among the youth. However, not much is known about the knowledge and attitude of youth towards contact lenses in Pakistan. This study targeted to assess the approach of youth in Karachi towards contact lenses and whether the differences noted in approach was simulated by gender. # Methods We conducted a cross-sectional survey in September 2018, using convenience sampling and interviewed 400 individuals, aged 16-25, to assess their knowledge, attitude, and practices towards contact lenses. The respondents were asked about their knowledge and its source. Attitudes were assessed by asking participants opinions, while practice question mainly focused on the recent (up to 1 month) use of contact lenses and their experience. Chi-square test was applied to cross-tabulate gender with knowledge, attitude, and practices of youth towards contact lenses. # Results The majority of the participants knew what contact lenses were (n=388, 97.0%) but did not know about the different materials of contact lenses available (n=280, 70.0%) and had learnt about them from their family (n=188, 47.0%). More than half of them (n=211, 52.8%) believed that the reason for contact lens use was to enhance physical appearance. An overwhelming majority stated that contact lenses should be cleaned daily (n=211, 52.8%) and they would never recommend contact lenses use in shower, pools or beaches (n=395, 98.8%). Only about one-third (n=126, 31.5%) of the participants stated that they wear contact lenses and a vast majority of them said that they wear them only on special occasions (n=88, 69.8%). Statistically significant differences were found with females knowing more about the possible side effects of using contact lenses (*P*=0.001) and being a current contact lens user (*P*\<0.001). # Conclusions This study shows that a lot of young adults residing in Karachi have significant knowledge about contact lens, however, their knowledge about its proper care and storage seems poor. Moreover, they seem to be non-compliant to the standard hygiene recommended by eye practitioners. Males and females had substantial differences in their outlook towards contact lenses and their use mainly due to the fact that females are more concerned about their physical appearance.